Protecting biodiversity outside natural forests: environmental-friendly oil palm plantations as an off-reserve strategy in Peninsular Malaysia - Azhar, B.; Mat, Sapari; S., Zulkifly; W. M., Suhailan; Sajap, Ahmad Said (Universiti Putra Malaysia Press, 2013)
Malaysian palm oil industry has been associated with tropical deforestation and faunal biodiversity loss. Despite the numerous forest reserves and protected areas, biodiversity conservation should be extended into agricultural areas including commercial oil palm. Scientific studies have clearly demonstrated that oil palm monocultures are poor substitute to natural forests. However, those studies have also indicated that oil palm-dominated landscapes support substantial biodiversity including forest species. With respect to ecological services, some species are known to be important in controlling pest outbreaks in oil palm plantations. Previous studies have shown that oil palm cultivations are effective carbon sinks. The central remaining knowledge gap of how palm oil-producing countries should conserve biodiversity within the existing oil palm plantations and smallholdings is addressed in this study. Thus, thematic review process that was organized around a topic of interest was used. In more specific, 53 journal articles investigating or highlighting the impacts of commodity crops cultivation on biodiversity were reviewed. It was proposed that oil palm-dominated landscapes be managed for conservation outcomes similar to that have been implemented in forest reserves and protected areas.